The Curse of Magical Realism? Latin American Literatures Today (KULT_online, 2016)
Since the boom period of magical realism during the 1960s and 70s, what has happened to the Latin American-German cultural transfers regarding literature? How is world literature defined, is Goethe’s idea of a literature of the world still relevant, and if yes, how exactly is that? From different angles – those of literary scholars on this and the other side of the Atlantic – by an editor and a literary translator as well as by several authors, the status quo of the literary exchange is described skillfully and thoroughly in the present publication to be reviewed here. It becomes clear that for a real dialogue to happen, beyond clichés and deep-rooted consumerism or reading habits, there remains a lot to do.